2016
DOI: 10.3892/mmr.2016.5219
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 promotes apoptosis and decreases invasion by upregulating the expression of ECRG4 in A549 human lung adenocarcinoma cells

Abstract: Abstract.Although Beclin 1 has been demonstrated to exert an important role in cell autophagy during carcinogenesis, its biological function in lung cancer has yet to be fully elucidated. A previous study by our laboratory identified that knockdown of Beclin 1 promoted cell growth and inhibited apoptosis in the A549 lung cancer cell line. In the present study, a Beclin 1 lentiviral expression vector was constructed, and an A549 cell line was established with a steady expression of Beclin 1. Furthermore, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This conclusion was consistent with previous researches in vitro, which showed that overexpression of Beclin-1 inhibited the proliferation and invasion of A549 human lung adenocarcinoma cells, while knockdown of Beclin-1 promoted the proliferation of A549 cells. 43 , 44 Another meta-analysis investigated the clinicopathological significance of Beclin-1 in gastric cancer, and reached similar conclusions. In that meta-analysis, high level of Beclin-1 was associated with better differentiation and earlier TNM stage, but the level of Beclin-1 was not associated with lymph nodal involvement.…”
Section: Discussionmentioning
confidence: 65%
“…This conclusion was consistent with previous researches in vitro, which showed that overexpression of Beclin-1 inhibited the proliferation and invasion of A549 human lung adenocarcinoma cells, while knockdown of Beclin-1 promoted the proliferation of A549 cells. 43 , 44 Another meta-analysis investigated the clinicopathological significance of Beclin-1 in gastric cancer, and reached similar conclusions. In that meta-analysis, high level of Beclin-1 was associated with better differentiation and earlier TNM stage, but the level of Beclin-1 was not associated with lymph nodal involvement.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, autophagic induction leads to decreased migration and invasion in glioblastoma cells, whereas autophagy deficiency increased cell motility and invasiveness [ 45 ]. In A549 human lung adenocarcinoma cells, Beclin1 promotes apoptosis and reduces invasion [ 49 ], whereas knockdown of Beclin1 decreased invasion and metastasis in osteosarcoma cells [ 50 ]. Our data clearly show that Beclin1 silencing led to reduced migration of osteosarcoma cells, and thus, it is likely that the effect of Beclin1 on cancer cell metastasis is cell type dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the function of Beclin1 in apoptosis has been investigated in many studies. A recent research showed that Beclin1 regulated apoptosis by binding to the anti-apoptotic members of the Bcl family such as Bcl-2, Bcl-xl and Bcl-w through the BH3 domain ( 9 ).…”
Section: Introductionmentioning
confidence: 99%